Gregarious Flowering of Thamnocalamus spathiflorus and T. falconeri, Bamboos from Uttaranchal, India - Naithani, H. B.; Pal, Mohinder; Lepcha, S. T. S. (Indian Forester, 2003)
Genus Thamnocalamus belongs to sub-family Bambusoideae. Three species viz. Thamnocalamus aristatus, T. falconeri and T. spathiflorus are known under this genus. This paper presents gregarious flowering in year 2002 of Thamnocalamus falconeri and T. spathiflorus from Uttaranchal, India. These species gregariously flowered after 28-33 years (T. falconeri) and 60 years (T. spathiflorus). Another two species viz. Drepanostachyum falcatum and Chimonobambusa anceps have already completed their flowering cycle in 1998 and 2000 and 1978 respectively. A key to the identification of the species, sub-species and varieties under Thamnocalamus is also provided.